Neglected Tropical Diseases (NTDs) in Saudi Arabia: Systematic Review and Meta-analysis - Najm Z. Alshahrani; Abdullah M. Alarifi; Abdullah M. Assiri (Journal of Epidemiology and Global Health)
Abstract Neglected tropical diseases (NTDs) pose a significant public health challenge in tropical and subtropical regions, particularly in the Kingdom of Saudi Arabia (KSA), where epidemiological data remain scarce. These diseases disproportionately affect vulnerable populations, leading to chronic morbidity and economic burdens. Understanding their distribution and burden is crucial for effective public health interventions. This study aimed to systematically evaluate the prevalence, distribution, and etiological patterns of NTDs in KSA, identifying key research gaps and informing future policy directions. A systematic review and meta-analysis were conducted on peer-reviewed studies published between 1950 and 2024 that investigated NTDs in humans in KSA. Ninety-four articles met the inclusion criteria. The majority (69.15%, n = 65) were published after 2010, with most studies concentrated in the western (n = 35, 37.23%) and southwestern (n = 15, 15.96%) regions, areas known for environmental and socioeconomic factors that may contribute to disease transmission. Protozoal NTDs were the most frequently reported (n = 28, 29.78%), followed by viral (n = 26, 27.66%), helminthic (n = 18, 19.15%), and ectoparasitic (n = 9, 9.57%) infections. Bacterial (n = 5, 5.32%), fungal (n = 4, 4.26%), and venom-related (n = 4, 4.26%) NTDs were less commonly reported. Meta-analysis yielded pooled prevalence estimates of leishmaniasis at 0.59 (95% CI: 0.38–0.77, I² = 94.2%) and dengue at 0.20 (95% CI: 0.05–0.53, I² = 98.8%), highlighting a substantial disease burden and high heterogeneity among studies. The findings emphasize the urgent need for strengthened national surveillance, improved diagnostic capacity, and region-specific interventions to control NTDs in KSA. Future research should focus on underrepresented regions, expand community-based epidemiological studies, and integrate cross-border surveillance strategies to mitigate disease importation risks. By addressing these gaps, KSA can enhance its preparedness and contribute to global NTD elimination efforts.